Alternative funding models for APC-free open access journals - De-Castro, Pablo (Anuario ThinkEPI, 2017)
The Alternative Funding Mechanism for APC-free Open Access journals and platforms implemented by the European Commission FP7 Post-Grant Open Access (OA) Pilot are described. This funding initiative, rolled out by the OpenAIRE project, aims to test the workflows around gold OA publishing, for titles that do not charge processing fees to their authors. The funding consists on specific technical improvements, according to plans proposed by journals and approved in previously selected bids. The main areas where these technical enhancements are being implemented are listed.